Gastroduodenal Obstruction Secondary to Pica-associated Bezoar: A Case Report - Mariam Attia; Ashley A. Lavoie-Forrest; Phoebe Langius; Leon Melnitsky; Sandra Lopez; Eric Boccio (Clinical Practice and Cases in Emergency Medicine)
Introduction: While mild or moderate iron-deficiency anemia may not cause any symptoms, more severe deficiencies may present clinically as fatigue, shortness of breath, exertional dyspnea, lightheadedness, tachycardia, and presyncope or syncope, and, in rare instances, pica. Pica is defined as the developmentally inappropriate ingestion of non-nutritive, non-food substances for more than one month. We present the case of a duodenal obstruction secondary to a pica-associated bezoar in a patient with iron-deficiency anemia who presented to the emergency department (ED) with abdominal pain. Case Report: A 40-year-old female with past medical history of iron-deficiency anemia, asthma, and Von Willebrand disease and allergies to both oral and intravenous (IV) iron presented to the ED with one day of acute and severe abdominal pain associated with nausea and vomiting. The patient’s last bowel movement was one day prior to presentation. The abdominal exam revealed mild distention and generalized tenderness with no evidence of rebound or guarding. Computed tomography of the abdomen and pelvis with IV and oral contrast demonstrated gastric distention and a fecalized distal duodenum with wall thickening concerning for a duodenal obstruction. Given the patient’s known history of iron-deficiency anemia, the emergency physician inquired about ingestion of non-nutritive substances to which the patient replied that she had been consuming cotton foam. The patient was admitted to the hospital for gastroenterology consultation and esophagogastroduodenoscopy. Conclusion: Pica-associated gastrointestinal bezoars are a rare complication with a variety of reported substances being consumed. Patients presenting with small gastroduodenal bezoars may benefit from endoscopic removal, but large non-fragmentable bezoars can only be removed through surgical intervention.